MOF-based stimuli-responsive controlled release nanopesticide: mini review - Hu, Shuhui; Yan, Chang; Fei, Qiang; Zhang, Bo; Wu, Wenneng (Frontiers in Chemistry, 2023)
By releasing an adequate amount of active ingredients when triggered by environmental and biological factors, the nanopesticides that respond to stimuli can enhance the efficacy of pesticides and contribute to the betterment of both the environment and food safety. The versatile nature and highly porous structure of metal-organic frameworks (MOFs) have recently garnered significant interest as drug carriers for various applications. In recent years, there has been significant progress in the development of MOFs as nanocarriers for pesticide applications. This review focuses on the advancements, challenges, and potential future enhancements in the design of MOFs as nanocarriers in the field of pesticides. We explore the various stimuli-responsive MOFs carriers, particularly focusing on zeolitic imidazolate framework-8 (ZIF-8), which have been successfully activated by external stimuli such as pH-responsive or multiple stimuli-responsive mechanisms. In conclusion, this paper presents the existing issues and future prospects of MOF-based nanopesticides with stimuliresponsive controlled release.